The Impact of Pain Invisibility on Patient-Centered Care and Empathetic Attitude in Chronic Pain Management - Emilie Paul-Savoie; Patricia Bourgault; Stéphane Potvin; Emilie Gosselin; Sylvie Lafrenaye (Pain Research and Management)
Objectives. The use of interdisciplinary patient-centered care (PCC) and empathetic behaviour seems to be a promising avenue to address chronic pain management, but their use in this context seems to be suboptimal. Several patient factors can influence the use of PCC and empathy, but little is known about the impact of pain visibility on these behaviours. The objective of this study was to investigate the influence of visible physical signs on caregiver’s patient-centered and empathetic behaviours in chronic pain context. Methods. A convenience sample of 21 nurses and 21 physicians participated in a descriptive study. PCC and empathy were evaluated from self-assessment and observer’s assessment using a video of real patients with chronic pain. Results. The results show that caregivers have demonstrated an intraindividual variability: PCC and empathetic behaviours of the participants were significantly higher for patients who have visible signs of pain (rheumatoid arthritis and complex regional pain syndrome) than for those who have no visible signs (Ehler–Danlos syndrome and fibromyalgia) (p<0.001). Participants who show a greater difference in their patient-centered behaviour according to pain visibility have less clinical experience. Discussion. The pain visibility in chronic pain patients is an important factor contributing to an increased use of PCC and empathy by nurses and physicians, and clinical experience can influence their behaviours. Thus, pain invisibility can be a barrier to quality of care, and these findings reinforce the relevance to educating caregivers to these unconscious biases on their behaviour toward chronic pain patients.